Pengaruh Agama dalam Sistem Pemerintahan Negara (Studi Kasus Sistem Pemerintahan Republik Islam Iran) - La Ode Machdani Afalah; Muhammad Tamar; Andi Murfhi (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2009)
Abstract: This paper on the role and position of the jurists in Iran Islamic government system and to investigate the implementation of the system of government in the Islamic Republic of Iran. In this research, descriptive research type use eksplanatif. In the view of the Shi'a Imami, there is a close connection between the concept of Imamate partner and the concept of Wilayat al-Faqih. Both are the successor to the prophetic mission of religion in order to preserve and manage the affairs of the world. The state becomes a tool and fortress as well as the retention erectly Sharia as a way of life of the people in achieving a happy life and Hereafter. Thus the State Islamic Republic of Iran to the wilayat al-faqih system has been institutionalized / institutionalization of religious values in the country's political structure.Keywords: religion, state, politic Abstrak: Tulisan ini mengenai peran dan kedudukan para fuqaha dalam sistem pemerintahan islam iran dan untuk mengetahui pelaksanaan sistem pemerintahan di negara Republik Islam Iran.  Dalam penelitian ini, menggunakkan tipe penelitian deskriptif eksplanatif. Di dalam pandangan kaum Syi’ah Imamiyah, terdapat kaitan yang sangan erat antara konsep Imamah dan konsep Wilayat al-Faqih. Kedua-duanya merupakan pelanjut bagi misi kenabian guna memelihara agama dan mengatur urusan dunia. Negara menjadi alat dan benteng pertahanan serta jaminan tetap tegaknya syariat sebagai pedoman hidup rakyat dalam mencapai kehidupan yang bahagia dunia dan akhirat. Dengan demikian Negara Republik Islam Iran dengan sistem wilayat al-faqih telah melakukan institusionalisasi/pelembagaan nilai-nilai agama dalam struktur politik negaranya.Kata kunci: agama, Negara, politik